Stance limb kinetics of older male athletes endurance running performance - Diss, C.; Gittoes, A. J.; Tong, R.; Kerwin, D. G. (Sports Biomechanics, 2015)
The aim of this study was to examine the age-based, lower limb kinetics of running performances of endurance athletes. Six running trials were performed by 24 male athletes, who were distinguished by three age groupings (S35: 26-32 years, M50: 50-54 years, M60+: 60-68 years). Lower limb coordinate and ground reaction force data were collected using a nine camera infra-red system synchronised with a force plate. A slower anteroposterior (M ± SD S35 = 4.13 ± 0.54 m/s: M60+ = 3.34 ± 0.40 m/s, p < 0.05) running velocity was associated with significant (p < 0.05) decreases in step length and discrete vertical ground contact force between M60+and S35 athletes. The M60+athletes simultaneously generated a 32% and 42% reduction (p < 0.05) in ankle joint moment when compared to the M50 and S35 athletes and 72% (p < 0.05) reduction in knee joint stiffness when compared to S35 athletes. Age-based declines in running performance were associated with reduced stance phase force tolerance and generation that may be accounted for due to an inhibited force-velocity muscular function of the lower limb. Joint-specific coaching strategies customised to athlete age are warranted to maintain/enhance athletes' dynamic performance.